The Contribution of Principal’s Academic Supervision and Pedagogical Competence to Teacher Performance - Awam, Rafizah; Rifma; Hadiyanto; Sabandi, Ahmad (Indonesian Research Journal in Education |IRJE|, 2023)
This research aims to analyze (1) the performance of SMPN [state junior high school] teachers, (2) the principal's academic supervision, and (3) pedagogical competence. This research uses a correlational quantitative method with an associative type. The population is 165 teachers at SMPN. Meanwhile, the samples were taken using a proportional stratified random sampling technique. The research instrument used a Likert scale model questionnaire. In addition, the test results show a valid. Next, the research data was analysed using the mean for data description, and test requirements, which are normality, homogeneity, independence, and linearity. The teacher performance results were 89.51%, academic supervision 85.00%, and pedagogical competence 79.66%. The results showed that the contribution of academic supervision to teacher performance was 13.10%. The pedagogical competence contribution to teacher performance was 16.60%, and the academic supervision and pedagogical competence contribution to teacher performance was 37.60%. The implications of the findings are also discussed.